Occupied Airwaves: Determinist Fantasies in the Radio Projects of Occupation and Anti‐Occupation. Issue 1 (April 2014) - King, Edward
Abstract In this article, I think about some of the ways in which the designs and fantasies surrounding radio infrastructures were shared by political and cultural movements either side of occupation, with particular attention to Algeria and Ireland. I ask what characterized these fantasies? How did they imagine new relations of space, time, and cultural integration? What kinds of assumptions about geography, people, and technology underpin these initial designs? How was radio instrumental to the imagining of possibly imminent futures in both colonial occupation and anticolonial resistance movements? I conclude that the material histories of radio reveal the way in which radio produced new communities of affiliation and belonging, beyond the bounds of the nation imagined by either colonial or anticolonial movements.